Pemodelan Proses Bisnis Sistem Akademik Menggunakan Business Process Modeling Notation - Denni Pratama; Yudhistira Arie Wijaya; Dian Ade Kurnia (LPPM STMIK IKMI Cirebon, 2022)
Based on observations and interviews, paper spending at XYZ High School reaches 65% of the total monthly office stationery budget, and this has been happening since 2008. Using paper as a document carries the risk of loss and damage and is problematic when stored. Search and find again. In addition, the raw paper material is trees, which currently coincide with environmental issues. Therefore, a circular economy needs to be applied to organizations to reduce the use of single-use items. The paperless movement can be implemented to reduce the use of paper, which a digital-based system has replaced. Implementing an integrated academic system through digital media is expected to reduce paper usage and dependence at XYZ High School and make the educational system's business processes more effective and efficient. Business Process Modeling Notation (BPMN) is used to design and model the academic system business processes at XYZ College. Through this BPMN, the business processes of the XYZ High School educational system can be clearly described, including the study plan system, lecture and exam scheduling system, lecturer assignment system, and study result assessment system. With the analysis and modeling of business processes and identification of system requirements in the XYZ High School academic system, it is hoped that it can be a proposal for improvement of existing business processes and also as the basis for developing the educational system at XYZ College and developing it into a good and reliable application product